Detecting altered postural control after cerebral concussion in athletes with normal postural stability. Issue 11 (21st October 2005) - Cavanaugh, J T; Guskiewicz, K M; Giuliani, C; Marshall, S; Mercer, V; Stergiou, N
Abstract : Objective: To determine if approximate entropy (ApEn), a regularity statistic from non-linear dynamics, could detect changes in postural control during quiet standing in athletes with normal postural stability after cerebral concussion. Methods: The study was a retrospective, case series analysis of centre of pressure (COP) data collected during the Sensory Organization Test (SOT) from NCAA Division I (USA) athletes prior to and within 48 h after injury. Subjects were 21 male and six female athletes from a variety of sports who sustained a cerebral concussion between 1997 and 2003. After injury, athletes displayed normal postural stability equivalent to preseason levels. For comparison, COP data also were collected from 15 male and 15 female healthy non-athletes on two occasions. ApEn values were calculated for COP anterior-posterior (AP) and medial-lateral (ML) time series. Results: Compared to healthy subjects, COP oscillations among athletes generally became more regular (lower ApEn value) after injury despite the absence of postural instability. For AP time series, declines in ApEn values were much larger in SOT conditions 1 and 2 (approximately three times as large as the standard error of the mean) than for all other conditions. For ML time series, ApEn values declined after injury in all sensory conditions ( F 1, 55  = 6.36, p = 0.02). Conclusions: Athletes who demonstrated normal postural stability after concussion nonetheless displayed subtle changes in postural control. Changes in ApEn may have represented a clinically abnormal finding. ApEn analysis of COP oscillations may be a valuable supplement to existing concussion assessment protocols for athletes.